2021
DOI: 10.3389/fmolb.2021.678701
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Small-Molecule Inhibitors of SARS-CoV-2 Proteins Using a Computational and Experimental Pipeline

Abstract: A rapid response is necessary to contain emergent biological outbreaks before they can become pandemics. The novel coronavirus (SARS-CoV-2) that causes COVID-19 was first reported in December of 2019 in Wuhan, China and reached most corners of the globe in less than two months. In just over a year since the initial infections, COVID-19 infected almost 100 million people worldwide. Although similar to SARS-CoV and MERS-CoV, SARS-CoV-2 has resisted treatments that are effective against other coronaviruses. Cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…ORF8 is also involved in suppression antiviral proteins from INFγ [14]. SARS-CoV-2 drug or vaccines were using spike protein as an important target [20,37,38,41], but ORF8 can be also targeted for producing therapeutic approaches. These studies shows that ORF8 is involved in modulating the host immune response and majorly by downregulating MHC-I.…”
Section: Introductionmentioning
confidence: 99%
“…ORF8 is also involved in suppression antiviral proteins from INFγ [14]. SARS-CoV-2 drug or vaccines were using spike protein as an important target [20,37,38,41], but ORF8 can be also targeted for producing therapeutic approaches. These studies shows that ORF8 is involved in modulating the host immune response and majorly by downregulating MHC-I.…”
Section: Introductionmentioning
confidence: 99%
“…Saquinavir was also indicated as a viable inhibitor of M pro after applying QSAR and HQSAR models [57] , while the latter compound was identified as an M pro inhibitor using molecular docking [58] . Candesartan cilexetil, which according to our study can inhibit spike from various lineages, had an IC50 value of approximately 67 μM against M pro in a FRET-based activity assay [59] . This drug can have a dual effect as it is used in high blood pressure treatment, which is also one of the hallmarks of COVID-19 due to the SARS-CoV-2 influence on the RSS.…”
Section: Discussionmentioning
confidence: 61%
“…In particular, recent studies have shown that vHTS-based methods are capable of identifying small-molecule inhibitors against SARS-CoV-2. 1 3 …”
Section: Introductionmentioning
confidence: 99%
“…3D-CNN-based approaches have been extensively used to predict the binding affinity of complexes. 1 , 14 Unlike the previous approaches, we propose to employ it as a pose classifier to filter out false positive docking poses to improve the accuracy of virtual screening. Moreover, as an alternative to the 3D-CNN-based method, we present another neural network approach (PCN) that directly captures global information on 3D atom structures without voxelizing them into a 3D voxel grid.…”
Section: Introductionmentioning
confidence: 99%